The Correlation of Students’ Vocabulary Mastery and Translation Ability at the Fourth Semester of English Education Program of Batanghari University - Nurul Fitri (Jurnal Ilmiah Dikdaya, 2023)
The purpose of this research is to find out the correlation of students’ vocabulary mastery and their translation ability at the fourth semester of English Education Program of Batanghari University. This research used quantitative method. The population of the data is the fourth semester students of English Education Program of Batanghari University meanwhile the technique of taking sample is cluster random sampling. The total sample of the research is 30 students and the instrument that used in this research is test for variable (X) and variable (Y). In calculating the data, SPSS 17.00 program with spearman rank technique analysis was used. The result showed that there was a significant correlation of students’ vocabulary mastery and their translation ability. Based on the indexes correlation table, the correlation coefficient in the value of 0.411 is in the range of indexes scale 0.400-0.600 which means that the correlation of vocabulary mastery (X) and translation ability (Y) is in Fair correlation, with the correlation coefficient is 0.411. In conclusion, the correlation is positive and can be categorized as fair correlation.